Detecting Clostridioides (Clostridium) difficile using canine teams: What does the nose know?. Issue 1 (March 2019) - Charles, M.K.; Wang, Y.; Zurberg, T.; Kinna, J.; Bryce, E.
Summary: Background: Trained canines are capable of detecting Clostridioides (Clostridium) difficile (CD) in the environment; however, the primary odour of interest on which the dogs alert is unclear. Aim: To evaluate the inter-rater reliability of two canine detection teams for their ability to discriminate between scent pads containing CD-toxin-positive and -negative odours and their ability to discriminate between clostridial strains. Methods: During a six-month period, two canine teams were tested weekly for their ability to detect CD-toxin-positive odours and discriminate between these and -negative odours. To further determine the canines' discrimination capability, scent pads impregnated with odours from reference isolates representing common CD toxin types (including toxin-negative CD isolates) or from clinical isolates representing other clostridial species were used. Results: A total of 264 samples were tested with an overall sensitivity of 94.7% (Team A) and 86.8% (Team B) and specificities of 96.9% and 98.7%, respectively. Inter-rater reliability was very good (Cohen's kappa 0.87). When challenged with toxin- and non-toxin-producing strains, the teams alerted on 96.3% of all CD isolate odours (including nontoxigenic strains) and 46.7% of closely related species. Conclusions: The canine teams exhibited strong inter-rater reliability on both clinical faecal specimens and reference CD isolates (both toxin and non-toxin producing) but were challenged to discriminate between CD and closely related clostridial species. These findings strongly support the development of scent detection programmes provided dogs and their handlers are properly trained and used in the right context.